2020
DOI: 10.3390/geriatrics5030053
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Visual and Auditory Distractions on Fistula Cannulation Pain among Older Patients Undergoing Hemodialysis: A Randomized Controlled Clinical Trial

Abstract: Pain associated with fistula cannulation is a challenge for nurses who provide care to older patients undergoing hemodialysis. Several non-pharmacological methods have been suggested for relieving fistula cannulation pain, but the benefits of visual and auditory distraction methods among older patients undergoing hemodialysis have not been investigated yet. Therefore, this study aimed to compare the effects of visual and auditory distractions on fistula cannulation pain among older patients undergoing hemodial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…The results of the risk of bias of the included studies are showed in Table 2. The randomisation process was rated low risk in eight studies because the randomisation was performed by sealed envelopes or coin toss or software random number table or block randomisation in the included studies (Aghbolagh et al, 2020; Babamohamadi et al, 2015; Burrai et al, 2019; Lin et al, 2012; Melo et al, 2018; Momennasab et al, 2018; Pothoulaki et al, 2008; Shabandokht‐Zarmi et al, 2017). This criterion was rated some concern in six studies due to no information about randomisation process (Babamohamadi et al, 2017; Burrai et al, 2014; Cantekin & Tan, 2013; Hou et al, 2017; Karadag & Karadakovan, 2015; Koca Kutlu & Eren, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of the risk of bias of the included studies are showed in Table 2. The randomisation process was rated low risk in eight studies because the randomisation was performed by sealed envelopes or coin toss or software random number table or block randomisation in the included studies (Aghbolagh et al, 2020; Babamohamadi et al, 2015; Burrai et al, 2019; Lin et al, 2012; Melo et al, 2018; Momennasab et al, 2018; Pothoulaki et al, 2008; Shabandokht‐Zarmi et al, 2017). This criterion was rated some concern in six studies due to no information about randomisation process (Babamohamadi et al, 2017; Burrai et al, 2014; Cantekin & Tan, 2013; Hou et al, 2017; Karadag & Karadakovan, 2015; Koca Kutlu & Eren, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies were examined the effect of music on AVF puncturerelated pain (Aghbolagh et al, 2020;Shabandokht-Zarmi et al, 2017).…”
Section: Pain and Arteriovenous Fistula Puncture-related Painmentioning
confidence: 99%
See 1 more Smart Citation
“…Three strategies have been identified in reducing pain during cannulation of the arteriovenous fistula for haemodialysis: (1) puncture technique, indicating the buttonhole technique as the one that translates a lower level of pain during cannulation; (2) use of non-pharmacological therapies, such as transcutaneous electrical stimulation, placing the users’ feet in hot water ten minutes before puncture, cryotherapy at the puncture site, acupuncture, audio-visual distraction techniques, and aromatherapy with lavender essence, or thermotherapy of the vascular access (of these, cryotherapy was identified as the technique that produced the best results in reducing the pain at the puncture of the vascular access); and (3) application of local anaesthetic before puncturing the venous access, identifying creams based on lidocaine and prilocaine (EMLA ® ) as ones that had the most effective results in reducing pain [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Distraction as a simple complementary and non-pharmacological approach can reduce pain severity and anxiety by drawing patients’ attention to pleasant stimuli [ 19 , 20 , 21 ]. Distraction inhibits the activity of the thalamus, insular cortex, and anterior cingulate cortex (ACC) and ultimately reduces pain [ 22 ].…”
Section: Introductionmentioning
confidence: 99%